Migratory diversity in an Arctic fish supporting subsistence harvest. (August 2020) - Hodgson, Emma E.; Hovel, Rachel A.; Ward, Eric J.; Lord, Sarah; Moore, Jonathan W.
Abstract: Arctic regions are warming more than twice as quickly as other parts of the globe, threatening Arctic fish and wildlife and the human communities that rely on them. Assessing species' vulnerability to this change requires understanding their life histories and ecology, including movement patterns and habitat use. However, this information has not been documented for many Arctic species, which may not follow predicable movements in these vast and changing landscapes. In the Gwich'in Settlement Area of western Canadian Arctic, one such species is łuk dagaii (in Gwich'in) or broad whitefish ( Coregonus nasus ). This species is the most important food fish for the Gwich'in Peoples of the region. We present results from a collaborative community-based research program established to build research capacity and address pressing research questions. Using otoliths extracted from fish caught by community monitors along the Peel River, we investigated migratory patterns using the isotopic ratio, 87 Sr/ 86 Sr. Applying a hidden Markov model to the otolith laser ablation transects, we explored emergent model states and linked them to regions of the watershed. Across and within individuals, fish occupied the ocean and three different identified freshwater locations; however, while all fish were captured in the Peel River, none expressed an otolith signature that would suggest they grew there. Across individuals, we found large variability in migratory patterns, suggesting that migrations are not obligate and that individual fish utilize the watershed very differently. This diversity may buffer whitefish and reliant human communities against change, but indicates dependence on a large, intact watershed. Highlights: Community-based research examined whitefish in an Arctic subsistence fishery. A hidden Markov model applied to otolith 87 Sr/ 86 Sr was used to infer fish migration. Migration varied widely across individuals indicating key life history biodiversity. Some Mackenzie River whitefish are anadromous, but many move extensively. Academic-Indigenous community partnerships can answer novel research questions.